2024
DOI: 10.3389/fmicb.2024.1309111
|View full text |Cite
|
Sign up to set email alerts
|

Association between the gut microbiota, inflammatory factors, and colorectal cancer: evidence from Mendelian randomization analysis

Mingwei Ma,
Zicheng Zheng,
Jie Li
et al.

Abstract: BackgroundColorectal cancer (CRC) is one of the most common malignant tumors primarily affecting individuals over the age of 50 years. Recent studies have suggested that the dysbiosis of the gut microbiota, a community of microorganisms in the human gut, is closely associated with the occurrence and development of CRC. Additionally, inflammatory factors (IFs) have also been reported to play a significant role in the development of CRC. However, the causal relationships between the gut microbiota, IFs, and CRC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Their findings suggested causal relationships between the intestinal microbiome and the risk of CRC. The results of this study revealed that dysbiosis of the intestinal microbiota may play an important role in development of CRC, suggesting their potential implications in CRC prevention [141]. Microbiome modulation was proposed as a new strategy for the prevention or treatment of CRC [136].…”
Section: Intestinal Microbiotamentioning
confidence: 82%
See 1 more Smart Citation
“…Their findings suggested causal relationships between the intestinal microbiome and the risk of CRC. The results of this study revealed that dysbiosis of the intestinal microbiota may play an important role in development of CRC, suggesting their potential implications in CRC prevention [141]. Microbiome modulation was proposed as a new strategy for the prevention or treatment of CRC [136].…”
Section: Intestinal Microbiotamentioning
confidence: 82%
“…Recent studies provide evidence on CRC-related species of the gut microbiota [139,140]. Ma et al performed a Mendelian randomization analysis to assess the relationship between gut microbiota and CRC [141]. They found a negative correlation between the Lachnospiraceae species and CRC risk, while the Porphyromonadaceae species, Lachnospiraceae UCG010 genus, Lachnospira genus, and Sellimonas genus had a positive relationship with the risk of CRC.…”
Section: Intestinal Microbiotamentioning
confidence: 99%